Knowledge of Pregnant Women in Regards to Oral Health of the Expected Child - PragyaPandey; Aseem Prakash Tikku; Ramesh Bharti; Prachi Jha; Diksha Singh; S Kudva (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Maternal oral health literacy, positive attitude and behavior in regards to infant’s oral healthdramatically reduce the chances of early childhood caries. The aim of the study is to assess oral healthknowledge among pregnant women and to report their beliefs regarding dental care for their expected child.The study also evaluates the contribution of health care providers in regards to the oral health of the expectedchild.Method: The cross-sectional study was conducted among 422 pregnant women, who attended an antenatalclinic at a tertiary health-care facility in Lucknow.Closed-ended questionnaire was used to collect the data. The validity and reliability of questionnaire wastested. Frequency, distribution tables and descriptive statistics were calculated for all variables. MannWhitney U test and Kruskal Wallis H tests were applied to check for any significant difference betweensocio-demographic characteristics and general knowledge about oral health care as well as practices. Bivariate and multivariate analysis was done.Result : 40.8% pregnant women had poor knowledge, 56% had poor oral hygiene practices and 46.8%had poor knowledge regarding dental care of their expected child. Education was the only factor to besignificantly associated with both variables- knowledge, and practice (p- value<0.01).Conclusion and Recommendation: The present study highlights the need for improved communicationand coordination between prenatal health care professionals, dentist, and pregnant women to facilitateoptimal care of their child’s oral health.